2020
DOI: 10.1186/s13287-020-01851-z
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-preconditioned human adipose-derived stem cells (HC016) increase their resistance to oxidative stress by overexpressing Nrf2 and bioenergetic adaptation

Abstract: Background: Mesenchymal stem cells, including those derived from human adipose tissue (hASCs), are currently being widely investigated for cell therapy. However, when transplanted at the site of injury, the survival and engraftment rates of hASCs are low, mainly due to the harsh microenvironment they encounter, characterized by inflammation and oxidative stress. To overcome these therapeutic limitations, cell preconditioning with lowconcentration of hydrogen peroxide (H 2 O 2) has been proposed as a plausible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…Finally, among the different co-cultures, the OX HOGd co-cultured with HC016 cells also exposed to oxidative stress showed a better recovery with enhanced viability (1.4-fold that in controls) and lower ROS levels (1.3-fold those in controls). As previously demonstrated, the 0.25 mM H 2 O 2 insult stimulated HC016 cell antioxidant response [ 18 ], and this seems to be beneficial for OX HOGd recovery.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Finally, among the different co-cultures, the OX HOGd co-cultured with HC016 cells also exposed to oxidative stress showed a better recovery with enhanced viability (1.4-fold that in controls) and lower ROS levels (1.3-fold those in controls). As previously demonstrated, the 0.25 mM H 2 O 2 insult stimulated HC016 cell antioxidant response [ 18 ], and this seems to be beneficial for OX HOGd recovery.…”
Section: Discussionsupporting
confidence: 56%
“…The preconditioning process–sub-lethal exposure to cellular stressors–promotes the expression and secretion of certain molecules that are required to reduce damage and increase survival, giving cells the capacity to respond efficiently to a higher level of the same stressor [ 15 , 16 , 17 ]. In a previous study, we showed that hASCs preconditioned with low doses of H 2 O 2 (HC016 cells) increase their resistance to oxidative stress by enhancing their intrinsic antioxidant capacity and bioenergetic regulation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 Under various pathologic conditions, the strong correlation between oxidative stress injury and nuclear factor E2-related factor 2 (Nrf2) has been previously proved. [13][14][15] The preceding study has pointed out that Nrf2/HO-1 pathway is one of the most recognized signaling closely associated with oxidative and anti-oxidative balance. 16,17 Under normal circumstances, the cap "n" collar subfamily of basic region-leucine zipper transcription factor Nrf2 is restricted in the cytoplasm by binding to its ligand Kelch-like ECH associating protein 1 (Keap1).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA sequencing was used to identify the cargos that might be responsible for the antioxidant potential of MSC-EVs. We compared the differentially expressed miRNAs between MSC-EVs and conditioned EVs (derived from H 2 O 2 -stimulated MSCs) 22 and found enrichment of specific miRNAs in MSC-EVs (Figure 2 A and B; Table S1 ); differential expression analysis revealed upregulation of many miRNAs (log2-fold change > 5: miR-215-5p, miR-424-5p, miR-31-3p, miR-193b-3p and miR-200b-3p) in H 2 O 2 -conditioned EVs (Figure 2 B). Gene Ontology (GO) classification (Figure 2 C; Table S2 ) revealed that the exosomal miRNA target genes (n = 58) were associated with the antioxidant activity molecular function.…”
Section: Resultsmentioning
confidence: 99%
“…To detect the antioxidant cargoes in MSC-EVs, MSCs were preconditioned with H 2 O 2 22 , 23 in FBS-depleted media, and EVs were isolated as described above. Total RNA from MSC-EVs (Control group, n = 3) and H 2 O 2 -preconditioned MSC-EVs (H 2 O 2 group, n = 3) was extracted using the miRNeasy Serum/Plasma Kit (217184, Qiagen, Germany), and the RNA integrity and concentration were examined by the Agilent 2100 Bioanalyzer (Agilent Technology, USA) and NanoDrop 2000 (Thermo Fisher, USA).…”
Section: Methodsmentioning
confidence: 99%